Two Distinct Mechanisms Govern RpoS-Mediated Repression of Tick-Phase Genes during Mammalian Host Adaptation by Borrelia burgdorferi, the Lyme Disease Spirochete - Arianna P. Grove (American Society for Microbiology, 2017)
ABSTRACT The alternative sigma factor RpoS plays a key role modulating gene expression in Borrelia burgdorferi, the Lyme disease spirochete, by transcribing mammalian host-phase genes and repressing σ70-dependent genes required within the arthropod vector. To identify cis regulatory elements involved in RpoS-dependent repression, we analyzed green fluorescent protein (GFP) transcriptional reporters containing portions of the upstream regions of the prototypical tick-phase genes ospAB, the glp operon, and bba74. As RpoS-mediated repression occurs only following mammalian host adaptation, strains containing the reporters were grown in dialysis membrane chambers (DMCs) implanted into the peritoneal cavities of rats. Wild-type spirochetes harboring ospAB- and glp-gfp constructs containing only the minimal (−35/−10) σ70 promoter elements had significantly lower expression in DMCs relative to growth in vitro at 37°C; no reduction in expression occurred in a DMC-cultivated RpoS mutant harboring these constructs. In contrast, RpoS-mediated repression of bba74 required a stretch of DNA located between −165 and −82 relative to its transcriptional start site. Electrophoretic mobility shift assays employing extracts of DMC-cultivated B. burgdorferi produced a gel shift, whereas extracts from RpoS mutant spirochetes did not. Collectively, these data demonstrate that RpoS-mediated repression of tick-phase borrelial genes occurs by at least two distinct mechanisms. One (e.g., ospAB and the glp operon) involves primarily sequence elements near the core promoter, while the other (e.g., bba74) involves an RpoS-induced transacting repressor. Our results provide a genetic framework for further dissection of the essential “gatekeeper” role of RpoS throughout the B. burgdorferi enzootic cycle. IMPORTANCE Borrelia burgdorferi, the Lyme disease spirochete, modulates gene expression to adapt to the distinctive environments of its mammalian host and arthropod vector during its enzootic cycle. The alternative sigma factor RpoS has been referred to as a “gatekeeper” due to its central role in regulating the reciprocal expression of mammalian host- and tick-phase genes. While RpoS-dependent transcription has been studied extensively, little is known regarding the mechanism(s) of RpoS-mediated repression. We employed a combination of green fluorescent protein transcriptional reporters along with an in vivo model to define cis regulatory sequences responsible for RpoS-mediated repression of prototypical tick-phase genes. Repression of ospAB and the glp operon requires only sequences near their core promoters, whereas modulation of bba74 expression involves a putative RpoS-dependent repressor that binds upstream of the core promoter. Thus, Lyme disease spirochetes employ at least two different RpoS-dependent mechanisms to repress tick-phase genes within the mammal.